Stigma Pekerja terhadap Penyandang Disabilitas di Tempat Kerja - Mustika, Ella Ayu Septia; Hadi, Ella N; Anharudin, Anharudin; Rofi’i, Aziz; Dewi, Siti Nurmala (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2022)
Background: Inclusiveness in the workplace for workers with disabilities is required and regulated by the government. However, workers with disabilities face challenges in fulfilling their right to obtain decent work and the stigma from colleagues. This situation affects the performance of workers with disabilities, which in the long run will affect company performance. Objective: This study aims to describe the stigma of workers against workers with disabilities in the workplace. Method: The study was a descriptive study with a cross-sectional study design. The population was workers working for at least three months. The sampling technique was accidental sampling by filling out a questionnaire through Google form with a total sample of 71 people. Results: The results showed that 30.99% of respondents had a high stigma, 40.85% of respondents had high negative attitudes, 38.03% of respondents had high discrimination, and 38.03% had low perceptions of justice towards workers with disabilities. Conclusion: Workers with disabilities experience stigma and discrimination in the workplace. This is one of the factors in the low absorption of the workforce at productive age groups with disabilities when compared to non-disabled groups.